Mediators’ Views of What Can Be Achieved Better in Initial Joint Sessions and in Initial Separate Caucuses - Roselle L. Wissler; Art Hinshaw (Washington University Journal of Law and Policy, 2023)
Over the past decade, the structure of the first formal mediation session has changed, with fewer traditional joint opening sessions and more separate caucuses to start the mediation. In light of these changes, the present Article explores whether mediators still see these two approaches as having the benefits conventionally ascribed to them, or whether they now see different advantages for each approach. The survey responses of over 700 experienced civil and family mediators from eight states show that mediators see several major differences in what can be better achieved in initial joint sessions and initial separate caucuses, respectively. Consistent with conventional wisdom, mediators said that initial joint sessions allow the parties to speak directly to and be heard by each other, and to develop a better understanding of the mediation process and the dispute, while initial separate caucuses permit the mediation to proceed when the parties are unable to mediate together civilly or meaningfully. Mediators noted multiple additional benefits associated with both parties hearing the same information at the same time in initial joint sessions, which previously have received little comment in the literature. Interestingly, mediators ascribed several other benefits to both initial joint sessions and initial separate caucuses, though generally for different reasons. Civil and family mediators differed in how often they mentioned some of the benefits for each approach. The present findings may encourage mediators and mediation trainers to revisit their views about the benefits they typically associate with initial joint sessions and initial separate caucuses and to weigh a broader set of considerations with the parties and lawyers when deciding how to begin the initial mediation session, allowing them to better tailor the mediation process to the needs of the particular case.
Keywords: mediation; joint session; initial; separate caucuses; formal mediation; joint opening session; mediators; process; litigation; civil matters; settlement; benefits; right to be heard; mediation process